2021
DOI: 10.1111/bcp.14710
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐man study to investigate safety, pharmacokinetics and exploratory pharmacodynamics of HTL0018318, a novel M1‐receptor partial agonist for the treatment of dementias

Abstract: HTL0018318 is a selective M 1 receptor partial agonist currently under development for the symptomatic treatment of cognitive and behavioural symptoms in Alzheimer's disease and other dementias. We investigated safety, tolerability, pharmacokinetics and exploratory pharmacodynamics (PD) of HTL0018318 following single ascending doses.Methods: This randomized, double-blind, placebo-controlled study in 40 healthy younger adult and 57 healthy elderly subjects, investigated oral doses of 1-35 mg HTL0018318. Pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 52 publications
(118 reference statements)
4
13
0
Order By: Relevance
“…The pharmacokinetics of HTL0018318 were well-characterized in plasma and urine. The characteristics were comparable to the pharmacokinetic data observed in previous studies [12,14]. Median t max (1.74-2.5 h) and mean halflife following the fifth dose (10.5-13.7 h) did not appear to change with respect to HTL0018318 dose level and co-dosing with donepezil.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The pharmacokinetics of HTL0018318 were well-characterized in plasma and urine. The characteristics were comparable to the pharmacokinetic data observed in previous studies [12,14]. Median t max (1.74-2.5 h) and mean halflife following the fifth dose (10.5-13.7 h) did not appear to change with respect to HTL0018318 dose level and co-dosing with donepezil.…”
Section: Discussionsupporting
confidence: 84%
“…The side effect profile observed in this study was comparable to that observed in the single ascending dose (SAD) and multiple ascending dose (MAD) studies with HTL0018318 [12,14]. Only nausea and vomiting were reported more frequently than in the SAD and MAD study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We previously reported the safety and tolerability of HTL0018318 following ascending doses in healthy subjects [21]. In this study, we report the safety and tolerability of HTL0018318 following multiple ascending dosing over 10 days in healthy younger adult and elderly subjects.…”
Section: Discussionmentioning
confidence: 84%
“…Pre-clinical studies have shown HTL0018318 to reverse scopolamine-induced deficits in passive avoidance learning in rats consistent with procognitive effects reported with other M 1 agonists on tests of learning and memory. The single ascending dose (SAD) study with HTL0018318 has shown that single doses of HTL0018318 up to 35 mg were relatively welltolerated in healthy younger adult and elderly subjects [21]. HTL0018318 was absorbed rapidly, peak plasma concentration was typically reached 1-2 h post-dose and the average elimination half-life was 12-16 h. Approximately 30% of the plasma unbound concentration entered the cerebral spinal fluid.…”
Section: Introductionmentioning
confidence: 99%